Improving Science Learning Capacity Through PjBL-Based Food Chain Media Training for Students of SMPN 3 Labuapi: Meningkatkan Kapasitas Pembelajaran IPA melalui Pelatihan Media Rantai Makanan Berbasis PjBL bagi Siswa SMPN 3 Labuapi - Wahyuni Arafani Arafani; Nurul Hidayah; Kadek Sukma Darma Putra; Aris Doyan; Mahrus Mahrus (Yayasan Siti Widhatul Faeha, 2025)
Learning media functions to facilitate students' understanding of scientific concepts in a concrete and visual way. PjBL is one of the learning models recommended in the independent curriculum. This model focuses on projects (real tasks). In this case, community service activities were carried out at SMP Negeri 3 Labuapi. The purpose of this activity is to determine the response and level of student satisfaction with the food chain board learning media. The activity method used is the service method which includes three steps, namely: preparation, implementation and evaluation. After the training activities were completed, all participants were asked to fill out a training assessment questionnaire. Then, the data obtained was analyzed descriptively and quantitatively. The results of this research show that students responded very well to the learning media that had been created and developed. This can be seen from the average score of 83.73% or rounded up to 84%, which is in the Strongly Agree category. Therefore, it can be concluded that the socialization activities and use of food chain board media located at SMP Negeri 3 Labuapi went very well and satisfactorily.